MENGUKUR KESIAPAN SEKOLAH UNTUK MENINGKATKAN EFEKTIFITAS PENERAPAN KURIKULUM MERDEKA DI SEKOLAH DASAR - Syofyan, Harlinda; Ainur Rosyid (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The study aims to assess the readiness of primary schools in Indonesia to effectively implement the Independent Curriculum, a recent education reform designed to promote flexibility and student-centered learning. Because the success of curriculum implementation depends on a variety of school-level factors, measuring institutional readiness is essential to ensure effective educational change. The research uses observation, interview, and comparative qualitative study methods to provide a comprehensive analysis of school readiness. This study involved 8 (eight) elementary schools, but differed in regional character, socio-economy, and student characteristics. Data collection methods included: (1) validated school readiness questionnaires given to principals and teachers of grades 1, 2, 4 and 5, who run an independent curriculum, (2) on-site observations of school infrastructure and resources, and (3) interviews with key stakeholders. The school readiness framework includes five dimensions: Achievement of Curriculum Aspects, Impact of the Implementation of the Independent Curriculum, Obstacles in the Independent Curriculum and Indicators of Necessary Interventions in the Independent Curriculum. In the Readiness Area that needs attention, among others, 75% of schools need to improve competence in learning and assessment, need to improve skills in teaching differentiated learning, and 50% of schools need to improve competence in the field of ICT. In terms of resources and infrastructure, schools need adequate availability of 37.5%, and then need academic support of 25% in the request for optimization of supervision assistance